Gestión de abastecimiento de la Ferretería Ferrecentro Jujan del Cantón Alfredo Baquerizo Moreno - Castro Junco, Lisbeth Mabel (2022)
The hardware store Ferrecentro Jujan, has as objective to analyze the factors that affect the supply management, an analysis was made with respect to the supply process in the company, the project was elaborated identifying critical elements at the moment of making a purchase, the management of inventories, as well as suppliers, raw materials and market strategy. As a proposal, a new purchasing process was designed with the objective of improving the hardware store's negotiation conditions and positively impacting inventory management and associated costs. From the operational point of view, all the processes for the reception and storage of raw materials are standardized, as well as the administrative part, where the inventory control model to be implemented and its associated costs are defined. Analyzing the processes of the supply system and having made the respective proposals, the management indicators are created where the main processes to be controlled are determined, each with a specific objective, a goal and proposed actions in case of not being fulfilled. The financial evaluation is a cost-benefit analysis of the project implementation. It allows defining whether or not it is financially acceptable to have a new supply system in the hardware store or to maintain the current conditions.